Physical, chemical and isotopic investigations of Ward Hunt Ice Shelf and Milne Ice Shelf, Ellesmere Island, NWT - Jeffries, Martin Orme (University of Calgary, 1985)
Bibliography: p. 291-310. The object of the research was to investigate the growth and structure of Ward Hunt and Milne Ice Shelves which have recently produced ice islands. The work involved ice core drilling and collection of snow and fiord water samples. These have been the subject of conductivity (SEC)-salinity, 180, tritium, ice density and ice texture analysis. Accorct;ng to these parameters, ten ice types have been identified (Tables 5.12A and 5.12B) and each is found in or adjacent to the ice shelves and plays a role in their growth and structure (Fig. 5.40). Ward Hunt Ice Shelf is largely composed of three types of basement ice, which are the product of a sequence of processes which transform first-year sea ice to very old multiyear sea ice, in the absence of 18 O depleted meltwater. Milne Ice Shelf is largely composed of glacier tongues which flowed into and coalesced in Milne Fjord. The ice tongues and the basement ice acted as stable platforms for further ice shelf thickening through snow and ice accumulation. The latter involved percolation and refreezing of meltwater, with attending isotopic homogenization and enrichment from snow o values of -31 .0 0 loo to ice o values of -29.2 0 loo. During periods of negative surface mass balance, meltwater accumulates in meltwater lakes in the summer and refreezes to trough ice (o 18 o, -24.0 °100) in the winter. The ice shelves act as dams creating stratified conditions of freshwater (runoff) overlying seawater (Arctic surface water and/or Atlantic water) in Disraeli Fjord and inner Milne Fjord. The freshwater just above the halocline is supercooled; frazil ice forms and floats to the surface and accretes as a freshwater fjord ice with a o1 8 O value of -26.0 0 loo. During a climatic amelioration ea. 250012000 BP to ea. 1600 BP, an extensive freshwater flow beneath Ward Hunt Ice Shelf led to the accretion of a freshwater, 18 O depleted ice (-25.5 0 loo), which originated with frazil ice growth, and is now sandwiched between basement ice layers. The ...